Ecology and the child: Determination of the knowledge level of children aged four to five about concepts of forest and deforestation - Ahi, Berat; Balcı, Sibel (Informa UK Limited, 2017)
The purpose of the study is to reveal the knowledge level of pre-school children aged four to five about the concepts of forest and deforestation. The study group of the research consists of 29 chi...
Keywords: Ecology; Environmental Education; Forest; Deforestation; Child; 4. Education; 8. Economic growth; 15. Life on land